PENGARUH KUALITAS PELAYANAN, TARIF, DAN LOKASI TERHADAP KEPUTUSAN PASIEN DALAM MENGGUNAKAN JASA RAWAT INAP PADA RUMAH SAKIT PERMATA MEDIKA SEMARANG - Fitria Apriliani Yulinda; Saryadi Saryadi; Bulan Prabawani (Universitas Diponegoro, 2016)
Hospital as one of the organization engaged in service activities can not be separated from a very tightcompetition between services, as more and more places of other health services. This study aimed to determinethe effect of service quality, rates and location of the decision to use the services of Gem Medika HospitalSemarang. Type of this research is explanatory research. Methods of data collection using interviews withquestionnaires. The sample in this study amounted to 100 respondents stratified sampling techniqueproportinate random. In linear regression analysis was used and the significance test by using SPSS 17.0. Fromthe analysis of the data found that in partial service quality has positive influence on decision to use services of57.5%, variable rates positive influence on the decision to use the services of 58.9%, and variable positiveinfluence on the location decision to use the services of 22.4 %. Simultaneously variable service quality, ratesand positive influence on the location decision of the use of services by 63.3%. To increase the quality ofservices namely by more maintain cleanliness inpatient rooms and also more attention to the attitude powermedical in serving patients .In addition a house party fixed pain needs to sustain offered rates and should alsothe hospital gems medika semarang increase accommodation vessel not unlike ambulance so that patientsemergency who their homes further away from the hospital. Gem medika could be immediately until to thehospital getting medical services.